THE RELATIONSHIP BETWEEN SELF ESTEEM AND FEAR OF MISSING OUT (FOMO) IN KPOP FANDOM SOCIAL MEDIA USERS - Siti, A'isah; Hazim, Hazim (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The purpose of this study is to determine the relationship between self esteem and Fear of Missing Out (FOMO) in Kpop fandom social media users. Method: This research method is quantitative correlation. The subjects amounted to 131 of the total population of 210 Kpop fandom people. The technique of determining the sample is done by cluster sampling. Analysis of the hypothesis of this study using product moment correlation test. Results: The results of hypothesis analysis, showed r = -0.788 and p < 0.001 (<0.05) which means there is a significant negative relationship between Self Esteem and FoMO in Kpop fandom social media users. Consequently, the higher the self esteem, the lower the FoMO in Kpop fandom social media users, and vice versa, the lower the self esteem, the higher the FoMO in Kpop fandom social media users. Novelty: The novelty in this study lies in its focus on examining the relationship between self esteem and FoMO in the Kpop fandom of social media users as well as focusing on the psychological dynamics of the Kpop fandom who have high emotional attachment to their idols, different from previous studies that generally discuss FoMO among adolescents or social media users in general.